Peran Manajemen Integral Pendidikan dalam Manajemen Kurikulum Berbasis Muatan Lokal di MI Tahfizhul Qur'an Asasul Huda Majalengka - Moch. Mahbub Jauhari; Muslihun Muslihun; Ashari Ashari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Local content-based education plays an important role in shaping students’ character while preserving regional cultural values. The success of local content curriculum implementation is determined not only by curriculum content but also by the effectiveness of educational management. This study aims to analyze the role of integral educational management in managing a local content-based curriculum at MI Tahfizhul Qur'an Asasul Huda Majalengka. This research employed a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation, then analyzed using the Miles, Huberman, and Saldana model consisting of data condensation, data display, and conclusion drawing. The findings reveal that integral educational management is implemented through the involvement of all school stakeholders in curriculum planning, implementation, supervision, and evaluation. The local content curriculum is developed contextually by integrating Sundanese language, Qur'anic memorization, and Islamic values into the learning process. Curriculum implementation is conducted systematically through special scheduling, regular supervision, and collaboration among school leaders, teachers, parents, and the community. The curriculum contributes positively to students’ religious character, discipline, appreciation of local culture, and cultural identity. These findings indicate that integral educational management significantly contributes to the effectiveness of local content curriculum management in Islamic elementary schools.